Management of the research nurse in the informed consent process in clinical trials - Maura Tamayo Rodriguez (Revista Cubana de Medicina Militar)
Informed consent is a process that consists of a dialogue between researchers and the patient about a certain procedure related to their health. In clinical trials, informed consent has a special connotation because it is research in which the efficacy and safety of a new product can be sought. The bioethical principles of autonomy, justice and beneficence have their maximum expression in these studies. The health professional must inform the patient and respect the decision she makes, in accordance with her values and her life project, as a clear expression of her moral autonomy. Historically, the process is led by the medical researcher, however, research nurses can assume responsibility in the process, as long as they are well prepared and trained in the problem under investigation, in good clinical practices and in current laws and procedures. The research nurse can lead the informed consent, just as the clinical researcher does.